The Role of the Blood Neutrophil-to-Lymphocyte Ratio in Aneurysmal Subarachnoid Hemorrhage - Cai, Lingxin; Zeng, Hanhai; Tan, Xiaoxiao; Wu, Xinyan; Qian, Cong; Chen, Gao (Frontiers in Neurology, 2021)
Aneurysmal subarachnoid hemorrhage (aSAH) is an important type of stroke with the highest rates of mortality and disability. Recent evidence indicates that neuroinflammation plays a critical role in both early brain injury and delayed neural deterioration after aSAH, contributing to unfavorable outcomes. The neutrophil to lymphocyte ratio (NLR) is a peripheral biomarker that conveys information about the inflammatory burden in terms of both innate and adaptive immunity. This review summarizes some relevant studies that associate the NLR with aSAH to evaluate whether the NLR can predict outcomes and be used as an effective biomarker for clinical management. The underlying pathophysiology is highlighted to identify new potential targets for neuroprotection and to develop novel therapeutic strategies.